93.4k views
1 vote
What is the inverse of the function f(x)=x+3

User Karstux
by
6.5k points

2 Answers

2 votes


f^(-1)(x) = x - 3

let y = x + 3 and rearrange making x the subject

x + 3 = y ← ( subtract 3 from both sides )

x = y - 3 ( change y to x )


f^(-1)( x) = x - 3


User Cliffroot
by
5.1k points
2 votes

Hello,

The inverse of the function is f^-1(X)=-3-x

How?

f (x)=-x-3

replace f(X) with y

y=-x-3

interchange the variables

x=-y-3

solve for y and replace f^-1 (X)


Hope this helps


User Cjstehno
by
5.0k points